Coboldus chazaroi, a new species of iphimediid amphipod (Amphipoda, Gammaridea, Iphimediidae) from a submarine cave, north Cuba - Ortiz, Manuel; Winfield, Ignacio; Varela, Carlos (Zootaxa, 2012)
The amphipods of Coboldus are considered as antipolar members of iphimediids with loss of a maxilla 1 palp article 2. Anew amphipod species of the genus Coboldus (Family Iphimediidae) collected from soft bottom in a submarine cave,Northern Cuba, is described. Coboldus chazaroi sp. nov., differs from all other known species by the following characters:pereonal dorsal processes bifid and equal in length, coxa 1 ventrally acute and bifid, article 5 of gnathopod 2 longer than6, dactylus longer than palm, posterior margin of pleonal epimeron 3 with 3 teeth, mandibular palp article 2 with 1 subdistal plumose seta, molar poorly developed with 1 basal seta, lacinia mobilis rectangular and finely serrate.